Contrast-enhanced ultrasound in liver cancer. (January 2015) - Leoni, Simona; Serio, Ilaria; Pecorelli, Anna; Marinelli, Sara; Bolondi, Luigi
SUMMARY : Contrast-enhanced ultrasound (CEUS) is a sure, noninvasive, repeatable imaging technique widely used in the characterization of benign and malignant liver lesions. The European Federation of Societies for Ultrasound in Medicine and Biology guidelines suggest the typical CEUS features of liver lesions as criteria for the noninvasive diagnosis in cirrhotic and not-cirrhotic patients. The clinical application of CEUS in the liver study is summarized in this review; the contrast-enhanced patterns of the most frequent liver lesions are described (hepatocellular and cholangiocellular carcinoma, liver metastases, hemangioma, focal nodular hyperplasia, adenoma). The role of this imaging technique in the diagnostic algorithm of liver malignancy is illustrated and the CEUS application in hepatologic and oncological settings is depicted.